Motivasi dan Kepercayaan Pasien untuk Berobat ke Sinse - Abdul Haris Jauhari 1 , Muhana Sofiati U Haris Jauhari, Muhana Sofiati Utami, Retna Siwi Padmawati (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Health service may not be obtained only from conventional medication but also traditional medication. The use of traditional medication is getting more popular. This may be supported by local culture and mass media. In Pontianak Municipality with major Chinese ethnic community, the use of Chinese traditional medication is very popular.Objective: The study was aimed at identifying motivation and trust of patients in seeking medication to sinshe.Method: This was a qualitative study using grounded theory approach. Location of the study was Pontianak Municipality. Informants consisted of 12 patients, 6 sinshe(s), 1 staff of health office, 1 doctor, and 1 leader of Chinese ethnic community. Samples were chosen purposively, using maximum variation sampling technique. Research instruments used were observation guide and in depth interview. Triangulation on methods and informants/source were used in examining the trustworthiness of the data. Data analysis was carried out through data transcript, coding, open coding, axial coding, data presentation, and making conclusion.Result: Patients trusted sinshe(s) due to their capabilities of curing chronic diseases. Patients had motivation to go to sinshe(s) because they failed in getting cure from conventional medication, they were worried in using chemical drugs and having operation and they were unsatisfied with conventional medication. According to patients, sinshes’ medication had many advantages, such as comprehensive, cheap and natural. However, there were also disadvantages, such as drugs were impractical, non hygienic, and did not taste good. Triggers which caused patients to go to sinshe were information supporting and culture, affordable cost, and experiences of the informants.Conclusion: Patients turned from conventional medication to sinshe (traditional) medication because of trust, motivation and trigger factors. Improving health service quality and health promotion should be made in order the community could get appropriate medication.Keywords: motivation, trust, patients, traditional medication, sinshe